Multi-Step Cellular and Tissue Selection of Soybean for Resistance to Osmotic Stress Using Peg 6000 Invitro Conditions - Mohammad Naim Noori (International Journal for Research in Applied Sciences and Biotechnology, 2021)
Cell and tissue selection in vitro allows targeted selection of the desired traits under severe selective conditions at the level of individual cells and tissues. On the basis of multistage cell and tissue selection with the use of a selective agent - neutral osmotic polyethylene glycol 6000 in increasing concentrations -5%, 10%, 15%, 20% of the final volume of the nutrient medium, callus of the Zhansaya soybean variety that are stably resistant to osmotic stress have been obtained. Regeneration from callus was noted only in8.3 % of the planted callus 6 soybean regenerants plants resistant to osmotic stress were obtained from callus.